Peningkatan Kesehatan Mental Siswa SMK Melalui Pendekatan Linguistik dan Konseling Bahasa di SMK An Naas Binjai - Rudi Purwana; Mariana Mariana; Asrul Asrul; Winda Novianti; Riani Baiduri Siregar; Heri Saputra (Lembaga Pengembangan Kinerja Dosen, 2025)
Mental health issues among vocational high school (SMK) students are becoming increasingly concerning, affecting their academic performance and overall well-being. This study explores the role of linguistic approaches and language counseling in improving students' mental health at SMK An Naas Binjai. The research employs a qualitative method, incorporating interviews, observations, and document analysis to understand how language influences students’ emotional expression, stress management, and social interactions. Findings indicate that a structured linguistic approach, including expressive writing, guided discussions, and positive communication strategies, helps students articulate their emotions better and develop coping mechanisms. Additionally, language counseling, which integrates psychological support with effective communication techniques, enables students to express their feelings constructively, reducing anxiety and enhancing self-confidence. The study highlights the importance of integrating language-based mental health interventions into the school curriculum to create a supportive learning environment. This research suggests that teachers and counselors should be trained in linguistics-based counseling techniques to provide more effective emotional support. Schools should also incorporate structured language activities that encourage open communication and emotional resilience. The findings contribute to the growing discourse on educational psychology by emphasizing the intersection of language, counseling, and mental health in vocational education settings.